Implementasi Nilai-Nilai Ahlussunnah Wal Jama’ah (ASWAJA) Dalam Pembelajaran Ke-NU-An di MTS Darussalam Kademangan Blitar - Abrori, M Sayyidul; Mispani, Mispani; Setiawan, Dedi; Khodijah, Khodijah (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2022)
The purpose of writing an article about the implementation of the values of ahlussunnah wal jama'ah (ASWAJA) in ke-NU-an learning at MTs Darussalam Kademangan Blitar is motivated by the inadequate quality of Islamic education output due to the degradation of morals and knowledge in education. The type of research used is a qualitative field research. The subjects in this study were the Principal, Deputy Head of Curriculum, ke-NU-an Teachers and Students. The results of his research include 1) The concept of ahlussunnah wal jama'ah (ASWAJA) which is applied is the concept of mabadi kahoiru ummah and ukhwah nahdliyah. 2) The implementation of the values of ahlussunnah wal jama'ah (ASWAJA) in ke-NU-an learning has three points: first, the implementation of values is tawasut realized in the form of amaliyah yasin and tahlil. Second, the implementation of thevalue is tasamuh realized by inculcating and implementing a high tolerance attitude between religious communities. Third, the implementation ofvalues is tawazun manifested in the form of amaliyah sholawat activities. 3) Evaluation of the implementation of the values of ahlussunnah wal jama'ah (ASWAJA) in ke-NU-an learning referring to KI-1 and KI-2 which was carried out using daily journals to see students' daily activities at the school. School and peer-to-peer assessments to find out student activities outside of school. The evaluation activities are implemented by the school and carried out by the teacher during each semester.